Inovasi Pendidikan Islam Di Ma’had Aly: Integrasi Tradisi Dan Modernitas - Arif Munzaki; Nur Cholid; Muh. Syaifudin (Journal of Innovative and Creativity, 2026)
This article examines the Islamic education model at Ma'had Aly as a representation of the integration between Islamic boarding school traditions and modern academic needs. Using a qualitative approach based on literature, this article analyzes the philosophical foundations, institutional structure, curriculum, learning methods, and the strengths and challenges of Ma'had Aly within the context of the national education system. The study results indicate that Ma'had Aly is capable of becoming an alternative Islamic education solution that not only maintains the depth of Salafiyah scholarship but also prepares students with critical thinking skills and scientific research capabilities. This model has significant prospects in producing scholars who are ready to face the challenges of the times and contribute to achieving the vision of Golden Indonesia 2045.